AB0049C INFLAMMASOME DRIVES RELEASE OF MITOCHONDRIAL DNA ENCLOSED IN EXTRACELLULAR MEMBRANE VESICLES AND PROPAGATION OF INFLAMMATION IN BEHÇET'S DISEASE. (June 2019) - konaka, hachirou; Takamatsu, Hyota; Park, Jeong-Hoon; Kato, Yasuhiro; Hirano, Toru; Kumanogoh, Atsushi
Abstract : Background: It has been reported that mitochondrial DNA (mtDNA) is released into the cytosol by mitochondrial stress and induces pro-inflammatory cytokine production via inflammasome and intracellular DNA sensors. Also, mtDNA in the extracellular space is known to result in sterile inflammation. However, the molecular mechanism of mtDNA release and its pathological significance in autoimmune diseases (ADs) has not been elucidated. Objectives: To clarify the molecular mechanism of mtDNA release and its pathological significance in ADs. Methods: We collected the serum from various AD patients and analyzed the levels of mtDNA in serum. We digested mtDNA in serum by DNase treatment. We purified the extracellular membrane vesicles (EMVs) and evaluated their inflammation-inducing potential. Also, we investigated the molecular mechanism behind mtDNA-induced inflammation by using inflammasome gene Knock out cell lines Results: We first measured the levels of mtDNA in serum of the various ADs by quantitative PCR and found that serum mtDNA levels were significantly high in BD. Interestingly, mtDNA in BD serum could not be digested by DNase treatment and was detected in the extracellular membrane vesicles (EMVs) purified by ultracentrifugation. Since EMVs are known to deliver various molecules from one cell to another, we stimulated monocytic cells with BD-derived EMVs and found that these EMVs could induce IL-1β production in an NLRP3 inflammasome-dependent manner. We then studied the mechanism of secretion of mtDNA in EMVs and found that both human primary monocyte and monocyte-like cell line released mtDNA-containing EMVs after stimulation with ATP or LPS. Further, BD-derived monocytes secreted more abundant mtDNA in EMVs than monocytes derived from healthy donors. Additionally, the inhibition of caspase-1 activity reduced the secretion of mtDNA in EMVs Conclusion: We revealed a novel mechanism of inflammation propagation involving inflammasome and mtDNA; activated inflammasome releases mtDNA-containing EMVs and subsequently leads to mtDNA-induced inflammation via NLRP3 inflammasome. Such inflammatory mechanism may contribute to the exacerbation of inflammation in BD. Disclosure of Interests: None declared